2020
DOI: 10.1007/s11695-020-04951-0
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Adjustable Gastric Banding to Roux-en-Y Gastric Bypass in One or Two Steps: What Is the Best Approach? Analysis of a Multicenter Database Concerning 832 Patients

Abstract: Background Roux-en-Y gastric bypass (RYGB) is often the preferred conversion procedure for laparoscopic adjustable gastric banding (LAGB) poor responders. However, there is controversy whether it is better to convert in one or two stages. This study aims to compare the outcomes of one and two-stage conversions of LAGB to RYGB. Methods Retrospective review of a multicenter prospectively collected database. Data on conversion in one and two stages was compared. Results Eight hundred thirty-two patients underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
(42 reference statements)
1
12
0
Order By: Relevance
“…Our results show that all the dimensions of quality of life are inversely related to weight regain and directly associated with physical activity ( Table 3 ). This aligns with previously published work reporting improvements in the quality of life of bariatric surgery patients that involved social life and work related with the practice of physical activity [ 39 ]. The sleep quality questionnaire indicated that the majority of these patients have poor sleep quality.…”
Section: Discussionsupporting
confidence: 90%
“…Our results show that all the dimensions of quality of life are inversely related to weight regain and directly associated with physical activity ( Table 3 ). This aligns with previously published work reporting improvements in the quality of life of bariatric surgery patients that involved social life and work related with the practice of physical activity [ 39 ]. The sleep quality questionnaire indicated that the majority of these patients have poor sleep quality.…”
Section: Discussionsupporting
confidence: 90%
“…The pooled data were merged in a single electronic database which managed to contain more than 1219 revisional procedures after LAGB, 189 of which (15.5%) underwent conversion to OAGB. 16,17 The aforementioned database includes demographic and medical data such as patient's age, gender, height, preoperative weight (before LAGB), date of LAGB placement, cause of conversion, date of LAGB removal, revisional procedure date, weight immediately before conversion to OAGB, and last weight recorded during follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…In our experience, we prefer the one-stage conversion of LAGB to RYGB. Conversion to RYGB has been advocated by many authors to be safe and effective for insufficient weight loss and band after LAGB [4,[11][12][13][14][15][16]. Also, data from systematic reviews have endorsed RRYGB for failed LAGB, and reported better and more sustained weight loss, and lower reoperation rates after RRYGB [7,19].…”
Section: Revision Surgerymentioning
confidence: 99%
“…Options for revision surgery usually included band removal, and conversion to laparoscopic RYGB or laparoscopic sleeve gastrectomy (LSG) [7]. RYGB has been endorsed by many authors as a safe and effective option for revision surgery after failed LAGB [4,[11][12][13][14][15][16]. Also, metaanalyses have shown the safety and effectiveness of RYGB after failed LAGB [7,[17][18][19][20][21].…”
mentioning
confidence: 99%
See 1 more Smart Citation